COMMON CAROTID INTIMA MEDIA THICKNESS IN OBESE CHILDREN BORN SMALL FOR GESTATIONAL AGE VERSUS APPROPRIATE FOR GESTATIONAL AGE - Ramona Stroescu; Ioana Micle; Teofana Bizerea; Monica Marazan; Maria Puiu; Gabriela Doros; Otilia Marginean (Amaltea Medical Publishing House, 2014)
The intima media thickness of the common carotid artery (CIMT) is a well-known marker of subclinical atherosclerosis. The "catch-up growth" phenomenon in children born small for gestational age (SGA) has been linked to early onset obesity with the subsequent emergence of metabolic syndrome (MetS). Aim: to determine the association between being born SGA and CIMT, a measure of atherogenesis and to establish cut off values for CIMT in obese children. Material and methods. A prospective study was carried out over a 1 year period (Jul 2012-June 2013). We analyzed 122 obese patients, 96 patients appropriate for gestational age (AGA) and 26 patients SGA. Both groups were matched for age, sex and BMI. CIMT was measured in all the patients. Using ROC curve, cut off values have been obtained for both groups. Results. CIMT in obese children born SGA was signifi cantly increased as compared with obese children born AGA similar age, sex and BMI (p = 0.0035). A CIMT cut off value of 0.049 cm has been obtained with a high sensitivity and specifi city. Conclusion. Being born SGA increases the atherogenic risk. CIMT is a well-known marker of subclinical atherosclerosis and is a noninvasive and inexpensive method for detecting development of subclinical atherosclerosis. Further population studies regarding reference values for CIMT in obese children born SGA and AGA are necessary.